(untitled) (TUTA Journal, 2022)
The Nepalese government for a sustainable economic development is also fully depended on the source of finance. The increasing rate of tax avoidance has been a key dare to the government in generating the income. Therefore tax avoidance or evasion is considered as a noteworthy issue in these days- a key to economic maturity. This paper judges the effects of tax avoidance on Nepalese economic developmental environment. Only one hundred fifty Nepali sensitive citizens have been administered with a structured questionnaire presented in front of tax payers and tax evaders. It has been found that the tax avoidance has adversely affected economic development, good governance and unpatriotic act of tax payers. On which basis the tax avoidance activities are carried out. Thus the study has recommended that the government should encourage sound governance system for the voluntary conformity of tax liability in the mind of tax payers.